Pengaruh Bagi Hasil, Kualitas Pelayanan Dan Brand Image Terhadap Keputusan Menjadi Nasabah Bank Syariah Dengan Motivasi Sebagai Variabel Intervening - Luthfi Sahra Nandia; Rifda Nabila (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2021)
This study aims to determine the effect of profit sharing, service quality and brand image on the decision to become a sharia bank customer with motivation as an intervening variable (a case study of the people of Salatiga city). This type of research is quantitative research using primary data. Processing this data using SPSS. The results of this study indicate that profit sharing and brand image have no influence on the decision to become a customer. Service quality and motivation have an influence on the decision to become a customer. Motivation can mediate profit sharing, service quality, and brand image on the decision to become a customer.